Civilisation recast theoretical and historical perspectives - Feuchtwang, Stephan 1937-; Rowlands, Michael ca. 20./21. Jh (Cambridge University Press, 2019)
Civilisation is a debated concept and is often associated with the prerogatives of the 'West', colonial histories, and even emerging global politics. In this book, Stephen Feuchtwang and Michael Rowlands use the examples of Africa and China to provide a new conceptualisation that challenges traditional notions of 'civilisation'. They explain how to understand duration and continuity as long-term processes of transformation. Civilisations are best seen as practices of feeding and hospitality, of rituals and manners of living and dying, of entering the portals into the invisible world that surrounds and encompasses us, of healing and the knowledge of the encompassing universe and its powers, including its ghosts and demons. Civilisations furnish the moral ideals for people to live by and aspire to and they are changed more by the actions of disappointed grassroots and their little traditions than by their ruling authorities. Just as they revitalise and change their civilisations, this book revitalises and changes the way to think about civilisations in the humanities, the historical and the social sciences
Title from publisher's bibliographic system (viewed on 15 Jul 2019)
Keywords: Geschichte; Civilization / History; Ethnology / Africa; Ethnology / China; Tradition; Zivilisation; Afrika; China